1995
DOI: 10.1016/0928-8244(95)00008-u
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae O139 produces a protease which is indistinguishable from the haemagglutinin/protease of Vibrio cholerae O1 and non-O1

Abstract: Haemaglutinin/protease (HA/P) is one of the virulence factors of Vibrio cholerae O1 and pathogenic strains of V. cholerae non-O1. In this study, we examined protease activity of a new serogroup of Vibrio cholerae recently designated as O139 synonym Bengal. The protease activity was produced by all eight isolates of V. cholerae O139 from Bangladeshi patients. Purification and partial characterization of the protease from V. cholerae O139 demonstrated the purified protease (O139-P) was indistinguishable from tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…We found that the biological activity of HA/P from V. cholerae O9 is indistinguishable from the biological activity of V. cholerae O139 or O1. These data are consistent with previously described data for classical HA/P activities (i.e., protease and hemagglutination activities) (10,17). The gene encoding HA/P has been cloned (9), and the predicted amino acid sequence is a 65-kDa protein.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We found that the biological activity of HA/P from V. cholerae O9 is indistinguishable from the biological activity of V. cholerae O139 or O1. These data are consistent with previously described data for classical HA/P activities (i.e., protease and hemagglutination activities) (10,17). The gene encoding HA/P has been cloned (9), and the predicted amino acid sequence is a 65-kDa protein.…”
Section: Discussionsupporting
confidence: 80%
“…HA/P has been considered a virulence factor of V. cholerae O1 and O139 and of V. cholerae non-O1 pathogenic strains (17). In vitro studies have demonstrated that HA/P cleaves a number of macromolecules, including ovomucin and fibronectin, which are found on the surfaces of intestinal epithelial cells, as well as lactoferrin, which is found in the intestinal lumen (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cultured in Casamino Acids-yeast extract broth, it produces a cytotonic enterotoxin (6), but in brain heat infusion broth, it produces an enterotoxin which is cytotoxic for Y1 adrenal tumor cells (2). It produces a hemagglutinin/protease which is identical to that produced by V cholerae 01 and non-O1 organisms (42). Even though the production of soluble hemolysin is inconsistent by the conventional tube test, all of the isolates tested to date have been positive for hemolysin by the CAMP test (2).…”
Section: Introductionmentioning
confidence: 99%